Members of the Polish Language Council on the Problems of Linguistic Diversity and Linguistic Inclusion in Poland - Wallas, Tadeusz (Social Inclusion, 2021)
The last couple of decades have brought a significant increase in personal movement from and to Poland. In consequence, it is very probable that the issues of linguistic diversity and linguistic inclusion more and more frequently will become subjects of multi-level and multi-institutional discussion reshaping the Polish public sphere. It is a matter of consideration which institutions will take leading positions in this debate, formulating main narratives and polemics. However, answering its advisory and opinion-making responsibilities, the Polish Language Council may be expected as one among the crucial actors in this discourse. The article presents pivotal attitudes of the Council’s members referring to the problem of linguistic diversity and linguistic inclusion in Poland. The presentation of the sources is combined with endeavours to answer the question: Do these materials allow considering the Council as a strong candidate for an essential designer of incoming public debate on linguistic diversity and linguistic inclusion in Poland? The research is conducted concerning the main assumptions of Joshua Fishman’s (1997) sociology of language and Harold Schiffman’s (2006) analysis of language policies as parts of linguistic cultures. Moreover, the methodological foundation of the text is supported by a general theoretical framework of historical institutionalism, and finally by Peter M. Haas’s conceptualisation of 'epistemic community.'